On Companion B-algebras (European Journal of Pure and Applied Mathematics, 2019)
This study introduces the concept of companion B-algebra and establishes some of its properties. Also, this paper introduces the notions of $\odot$-subalgebra and $\odot$-ideal of a companion B-algebra and investigates their relationship. Furthermore, this study establishes some homomorphic properties of $\odot$-subalgebra and $\odot$-ideal.
Keywords: companion B-algebra; $\odot$-subalgebra; $\odot$-ideal; companion B-homomorphism